2021
DOI: 10.1002/agm2.12149
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and cardiovascular problems in elderly patients: Food for thought

Abstract: The global number of COVID‐19 infections, as of December 23, 2020, stood at approximately 79 million, with over 1.7 million deaths. The development of vascular inflammation may also contribute to a hypercoagulable state and endothelial dysfunction in such patients. It is known that multi‐organ damage is more likely in patients with sepsis if they develop coagulopathy and that inhibition of thrombin synthesis can have a positive impact in reducing mortality. In this review, we will focus on the protection of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This evidence occurred despite the increased clinical and pharmacological experience and the start of the immunization program in December 2021 in Italy. Many risk factors have been associated with acute respiratory distress syndrome development and worsened clinical outcomes from COVID-19 [ 17 , 18 , 19 ]. As shown in previous papers, some comorbidities are closely related to intensive care admission and poor prognosis (e.g., hypertension, CLD, diabetes, and CKD) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This evidence occurred despite the increased clinical and pharmacological experience and the start of the immunization program in December 2021 in Italy. Many risk factors have been associated with acute respiratory distress syndrome development and worsened clinical outcomes from COVID-19 [ 17 , 18 , 19 ]. As shown in previous papers, some comorbidities are closely related to intensive care admission and poor prognosis (e.g., hypertension, CLD, diabetes, and CKD) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Often, those highly vulnerable present with common comorbidities not limited to chronic heart disease, arrhythmias, cardiomyopathies, diabetes, coagulopathy, hypertension, and immuno-senescence. Followed by severe infection during the early phases of contracting the virus, patients may have a direct cardiac injury, increased inflammation, endothelialitis, and a cytokine storm (Costa et al, 2021).…”
Section: Geriatric Carementioning
confidence: 99%
“…Another study conducted by Costa suggested that patients with cardiovascular comorbidities such as hypertension and coronary heart disease (CHD) are more at risk for more severe manifestations if infected with SARS-CoV-2 and contribute to the majority of deaths in COVID-19. This is thought to be due to higher ACE2 expression in patients with cardiovascular disease (Costa, 2020). Continuously high blood pressure causes damage to the arterial system slowly.…”
Section: Funnel Plotmentioning
confidence: 99%